2020
DOI: 10.1038/s41598-020-76602-4
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of ballast-mediated species transfer reveals important introduction and dispersal patterns in the Arctic

Abstract: Rapid climate change has wide-ranging implications for the Arctic region, including sea ice loss, increased geopolitical attention, and expanding economic activity resulting in a dramatic increase in shipping activity. As a result, the risk of harmful non-native marine species being introduced into this critical region will increase unless policy and management steps are implemented in response. Using data about shipping, ecoregions, and environmental conditions, we leverage network analysis and data mining te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The standards are different for two categories of “viable organisms” and three categories of “indicator microbes”. These regulations are uniform across ports, but HAOP spread risks vary at different locations. Stricter regional regulatory standards may be needed to achieve better protection for certain ports, particularly those with high HAOP spread risk or those that serve as key hubs in the global shipping network.…”
Section: Introductionmentioning
confidence: 99%
“…The standards are different for two categories of “viable organisms” and three categories of “indicator microbes”. These regulations are uniform across ports, but HAOP spread risks vary at different locations. Stricter regional regulatory standards may be needed to achieve better protection for certain ports, particularly those with high HAOP spread risk or those that serve as key hubs in the global shipping network.…”
Section: Introductionmentioning
confidence: 99%
“…The use of opportunistic network analyses built on eDNA metabarcoding studies could represent a valuable asset to generate an extensive baseline of simplified food web reconstructions, which could help environmental scientists and practitioners monitor a larger portion of our seas and flag possible ongoing anthropogenic disturbance (DiBattista et al., 2020; Gilarranz et al., 2016). These rapidly generated networks have the potential to unveil processes such as the loss of keystone species (Wu et al., 2020), the impact of expanding/invasive species (Saebi et al., 2020), the detrimental impacts of environmental changes on top predators (Sagarese et al., 2017), the depletion of forage taxa that sustain commercially important resources (Lassalle et al., 2011), the ecosystem‐level effect of marine protection (Casselberry et al., 2020), and a variety of other ecological processes that are often latent and difficult to unpick over timescales that are relevant to management.…”
Section: Benefits Caveats and Future Stepsmentioning
confidence: 99%
“…The study found that the global shipping network exhibits the small-world property and that there were substantial differences between how ships carrying different cargo navigated the network, suggesting implications for the spread of invasive species through ship ballasts. This latter result was built upon in [7,17] (among others), where a network approach was again applied to AIS data to study the transfer of invasive species in ballasts of ships. The second study used techniques from higher-order network analysis, specifically the variable-order network model developed in [18], to show that incorporating sequential information improves prediction of invasive species movements.…”
Section: Global Liner Shipping Networkmentioning
confidence: 99%